Implementasi Kurikulum Merdeka dalam Pembelajaran Bahasa Inggris di SMKN 02 Kota Bengkulu - Basinun Basinun; Ivanda Tegar; Muhammad Yusuf Afif; Haruwan Lupiarto Reza Susangkut (UIN Fatmawati Sukarno Bengkulu, 2025)
Abstract: The implementation of the independent curriculum has not been effective, as indicated by the fact that educators have not been able to provide freedom to students and educators have not been able to determine the methods, objectives, and models of learning. The purpose of this study was to evaluate the implementation of the independence curriculum in English learning at SMKN 02 Bengkulu City. Using a descriptive qualitative method with information sources obtained through observation, surveys, and literature studies. The results of the study show that the implementation of the independent curriculum in general has been carried out but is still not effectively implemented by the school. The implementation of the independent curriculum does not meet the learning expectations that should be implemented by focusing more on students, but in the field the role of teachers still dominates the classroom. In this curriculum, students are still less free to learn English well. Thus, it can be concluded that the implementation of the independent curriculum in general has been carried out but has not been effective. The recommendation of this study is to conduct an assessment of the use of the independent curriculum implemented at SMKN 2 Kota Bengkulu.Keywords: Implementation of Independent Curriculum, English Language Learning.Abstrak: Implementasi kurikulum merdeka beluf efektif ditandai bahwa tenaga pendidik belum mampu memberikan keleluasaan kepada peserta didik dan tenaga pendidik belum mampu menentukan cara, tujuan, dan model pembelajaran. Tujuan penelitian ini untuk mengevaluasi implementasi kurikulum merdeka dalam pembelajaran Bahasa Inggris di SMKN 02 Kota Bengkulu. Menggunakan metode kualitatif deskriptif dengan sumber informasi yang didapat melalui pengamatan, survei, dan studi pustaka. Hasil penelitian menunjukkan bahwa implementasi kurikulum merdeka secara umum sudah dilakukan namun masih belum efektif di laksanakan oleh pihak sekolah. Pelaksanaan kurikulum merdeka tidak memenuhi ekspetasi pembelajaran yang seharusnya dilaksanakan dengan lebih memfokuskan kepada siswa, namun pada lapangan peran guru masih mendominasi ruang kelas. Dalam kurikulum ini, siswa masih kurang leluasa mempelajari Bahasa Inggris dengan baik. Dengan demikian dapat disimpulkan bahwa implementasi kurikulum merdeka secara umum sudah dilakukan namun belum efektif. Rekomendasi penelitian ini adalah untuk melakukan penilaian terhadap penggunaan kurikulum merdeka yang dilaksanakan di SMKN 2 Kota Bengkulu.Kata kunci: Implementasi Kurikulum Merdeka, Pembelajaran Bahasa Inggris.